Kosmologi Filsafat Proses dan Ekologi Integral Laudato Si’: Suatu Perbandingan tentang Implikasi bagi Isu Lingkungan Hidup - Johanis Ohoitimur; Damianus Pongoh; Paulina Kuntag; Anita Stephanie F. Warow (Jurnal Seri Mitra (Refleksi Ilmiah Pastoral), 2026)
This article examines the similarities and differences between the environmental implications of Alfred North Whitehead’s cosmology and the concept of integral ecology articulated in Pope Francis’s encyclical Laudato Si’. Employing a comparative-interpretive literature review, it argues that both Both perspectives provide conceptual resources for criticizing mechanistic, dualistic, and anthropocentric paradigms that reduce nature to an object of human exploitation. Whitehead’s process philosophy understands reality as a dynamic network of interrelated events, whereas Laudato Si’ presents the world as God’s creation, whose interconnected elements constitute a single “common home”. Their principal similarities lie in their emphasis on relationality, the intrinsic value of the natural world, their critique of the technocratic paradigm, and their implication on ecological responsibility. Nevertheless, they differ significantly in their metaphysical, theological, and ethical foundations. Whitehead develops a process metaphysics in which reality is constituted by becoming and relationality, while Laudato Si’ is grounded in the theology of creation, the dignity of the human person, the common good, and humanity’s moral responsibility before God. The novelty of this article lies in its systematic mapping of the similarities and differences between the two approaches in terms of their ontological foundations, conceptions of God, understandings of the human position, normative foundations of ecological ethics, and ultimate visions of the cosmos and creation.